Parts of Speech - Ansaldo, Umberto (John Benjamins Publishing Company, 2010)
Should Parts of Speech be treated as descriptive tools or are they to be considered universal constructs? Should they be defined semantically, syntactically, or otherwise? And do non-Indo-European languages reveal novel aspects of categorical assignment? This book attempts to answer these and other fundamental questions for linguistic theory.